1971
DOI: 10.1192/bjp.118.546.509
|View full text |Cite
|
Sign up to set email alerts
|

Extrapyramidal Disorders After Prolonged Phenothiazine Therapy

Abstract: Motor disorders occurring in association with phenothiazine therapy have been widely appreciated and investigated since the advent of these drugs in the early nineteen-fifties. Published works have indicated that between 20 and 40 per cent of patients treated with phenothiazines exhibit signs of extrapyramidal dysfunction (Denham, 1961; Ayd, 1961). However, the relationship between treatment variables and the frequency of these motor disorders is not a simple one. Many factors are likely to have aetiological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

1972
1972
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(24 citation statements)
references
References 6 publications
1
20
0
3
Order By: Relevance
“…Neuroleptic drug treatment in humans can cause several motor dysfunctions, some of which are persistent or irreversible (Ayd, 196 1;Druckman et al, 1962;Crane et al, 1971;Kennedy et al, 1971;Burke et al, 1982). These include tardive dyskinesia and acute and late-onset dystonias.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroleptic drug treatment in humans can cause several motor dysfunctions, some of which are persistent or irreversible (Ayd, 196 1;Druckman et al, 1962;Crane et al, 1971;Kennedy et al, 1971;Burke et al, 1982). These include tardive dyskinesia and acute and late-onset dystonias.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroleptic-induced Parkinsonism is common; the lowest estimate is 23% (Ayd, 1961), but Kennedy et al (1971) found that 88% of chronic schizophrenics after at least three months of treatment with a phenothiazine had tremor, and 68% had rigidity. Many studies of drug-induced Parkinsonism have employed techniques somewhat different from those in idiopathic Parkinson's disease.…”
Section: Ticsmentioning
confidence: 99%
“…It is fairly simple to apply, the terms used are clearly defined, and there is a standardised examination procedure. The scale includes global assessments of severity (both by the patient and the observer) and dyskinesia scores for the face, lips, jaw, tongue and limbs, as well as a functional disability score (see also Kennedy, Hershon & McGuire, 1971).…”
Section: Ticsmentioning
confidence: 99%
“…In fact, Crane and Smeets (1974) found that moderate and severe T.D. were detected only in persons who had received a minimum of 14 g of chlorpromazine equivalent with a maximum daily dose of 72 mg. Kennedy et al (1971) worked the dosage and T.D. correlation by analys ing the relationship of the cluster of symptoms with the dosage.…”
Section: Etiological Factors Medicationmentioning
confidence: 99%